Audiovisivi e didattica universitaria. Un nuovo modello di integrazione - D'Agostini, Marco (Studi sulla Formazione/Open Journal of Education, 2021)
The article aims to establish the validity of a university teaching method, called Learning by Film (LbF), which integrates the use of the audiovisual tool in the "classic" university lectures. After an analysis of the pedagogical and neuroscientific aspects related to the use of audiovisual in educational and school contexts, the central part of this work deals with describing and analyzing the experience in the Communication course of the University of Udine (Department of Medical Area) in the academic year 2019-2020. The proposed method (Learning by Film) was evaluated with two main tools: the first to indicate the depth and effectiveness of the analysis of the films by the students; the second, through a questionnaire, to highlight the potential and criticality of the method in a perspective of integrative improvement of university teaching. All with the aim of actively involving learners and making the transmission of knowledge a more engaging and effective activity for both students and teachers.